A Novel UPLC-MS/MS Assay for the Measurement of Linezolid and its Metabolite PNU-142300 in Human Serum and its Application to Patients With Renal Insufficiency - Wang, Yingying; Gu, Er-min; Du, Xiaoxiang; Xu, Ren-ai; Lin, Guanyang (Frontiers in Pharmacology, 2021)
The contribution of the metabolites of linezolid to the associated myelosuppression is unknown in patients who are renal impairment. In this research, the purpose of our experiment was to explore and develop a quick and robust ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) assay for the determination of linezolid and its metabolite PNU-142300 in human serum simultaneously. The analytes were prepared using a simple and convenient approach with acetonitrile for protein crash, and then separated from the matrix on a Waters Acquity UPLC BEH C18 (2.1 mm × 50 mm, 1.7 μm) column in a program of gradient elution, where the mobile phase was consisted of water with 0.1% formic acid and acetonitrile, and was placed at 0.40 mL/min flow rate. Multiple reaction monitoring (MRM) was employed and conducted for UPLC-MS/MS detection with ion transitions at m/z 338.01 → 296.03 for linezolid, m/z 369.96 → 327.98 for PNU-142300 and m/z 370.98 → 342.99 for tedizolid (Internal standard, IS), respectively. This method had good linearity respectively in the calibration range of 0.01-20 µg/mL for linezolid, and 0.05-100 µg/mL for PNU-142300. In the intra- and inter-day, the precision of linezolid and PNU-142300 was below 14.2%, and the accuracy in this method was determined to be from -9.7% to 12.8%. In addition, recovery and matrix effect of the analytes were all found to be acceptable, and the analytes during the assay and storage in serum samples were observed to be stable. The novel optimized UPLC-MS/MS assay was also successfully employed to determine the concentration levels of linezolid and PNU-142300 in human serum. The results showed that linezolid-associated myelosuppression occurs more frequently in patients with renal insufficiency, and the metabolite-to-parent concentration ratio of PNU-142300 is predicted to reduce this toxicity of myelosuppression.